2011
DOI: 10.1111/j.1365-2672.2011.05184.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable agronomic practices, cultivar, strain source and initial contamination dose differentially affect survival of Escherichia coli on spinach

Abstract: Aims:  Greenhouse and field trials were conducted under different agronomic practices and inoculum doses of environmental Escherichia coli and attenuated E. coli O157:H7, to comparatively determine whether these factors influence their survival on leaves and within the rhizosphere. Methods and Results:  Hydroponic conditions: E. coli spray‐inoculated at log 4 CFU ml−1 was recovered from leaf surfaces at a mean population of 1·6 log CFU g−1 at 15 days. E. coli O157:H7 sprayed at log 2 or 4 CFU ml−1 levelled off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…However, this variable dropped during multivariable modeling where we also considered weather (precipitation over the past month before sampling). This is in agreement with the study by Gutiérrez-Rodríguez et al (45), which reported water availability as the dominant factor in survival of E. coli in a field trial; water availability depends on irrigation, which in turn depends on the local weather (precipitation) providing the rationale for the link between spinach contamination probability and weather. Overall, these results suggest that the time since planting of spinach is a useful predictor of the probability of spinach contamination, albeit its predictive ability compared to those of other considered risk factors (e.g., precipitation) seems lower.…”
Section: Discussionsupporting
confidence: 82%
“…However, this variable dropped during multivariable modeling where we also considered weather (precipitation over the past month before sampling). This is in agreement with the study by Gutiérrez-Rodríguez et al (45), which reported water availability as the dominant factor in survival of E. coli in a field trial; water availability depends on irrigation, which in turn depends on the local weather (precipitation) providing the rationale for the link between spinach contamination probability and weather. Overall, these results suggest that the time since planting of spinach is a useful predictor of the probability of spinach contamination, albeit its predictive ability compared to those of other considered risk factors (e.g., precipitation) seems lower.…”
Section: Discussionsupporting
confidence: 82%
“…Season-to-season variability in the susceptibility of crops to colonization by Salmonella and enterohemorrhagic E. coli pre-and post-harvest have been previously reported (Gutierrez-Rodriguez et al, 2012;. Salmonella proliferation was the highest in fruits harvested in Spring 2011 and Fall 2012 (harvests A and D, Fig.…”
Section: Seasonal Variability and Susceptibility Of Tomatoes To Infecmentioning
confidence: 86%
“…While the occurrence of the pathogen in leafy greens on that same sample date was relatively low, subsequent dissemination of high levels of E. coli O157:H7 from the feedlot surface to the plots may have increased the contamination of leafy greens that were sampled on the later dates. Numerous studies have evaluated the risks associated with preharvest contamination of leafy vegetables and have found that E. coli O157:H7 can persist on spinach and lettuce for days up to weeks (31)(32)(33)(34)(35)(36)(37)(38). Both growth chamber and field studies indicate that after inoculation onto leafy greens to mimic a contamination event, populations of E. coli O157:H7 initially decrease rapidly, followed by a more gradual rate of decline of remaining cells.…”
Section: Resultsmentioning
confidence: 99%